EPCT-24 THE REMIND TRIAL: MULTI-ANTIGEN TARGETED T CELLS FOR PEDIATRIC CNS TUMORS. (1st June 2021) - Grant, Melanie; Fortiz, Maria; Wang, Lu; Lang, Haili; Datar, Anushree; Reynolds, Emily; Terpilowski, Madeleine; Geiger, Ashley; Lazarski, Chris; Tanna, Jay; Pitino, Adriana; Zhang, Nan; et al.
Abstract: Background: Patients with relapsed CNS malignancies or DIPG face terrible prognoses. We hypothesized that T cells specific for 3 tumor-associated antigens (TAA), WT1, PRAME and survivin, would be safe and elicit anti-tumor immunity. Methods: Patients (n=18) received autologous tumor antigen-associated T cells (TAAT) (up to 8x10 7 /m 2 ) for newly diagnosed DIPG (Group A) or recurrent CNS malignancies (Group B) on a Phase I dose-escalation study (NCT03652545) and were monitored for safety and response. Results/Discussion: 16/18 patients who received TAAT completed the 45-day safety monitoring phase with no dose-limiting toxicities. Adverse events were minimal despite multiple pretreatments in Group B. Infused cells were predominantly CD3+ T cells (median 96%; range: 87–99%), with CD4+ and CD8+ comprising 16% (range: 5–87%) and 40% (range: 4–67%) respectively. Specificity for 1–3 TAAs was demonstrated in 11/18 TAAT by a-IFN-γ ELISPOT. Dose escalation is complete, and clinical and immunologic response assessments are ongoing. Plasma cytokine and proteomic analyses demonstrated dynamic post-infusion immune cytokine and protein responses. Consistent with an infusion-mediated immune response all patients in Grp A showed increased T cell effector, inflammatory and immune-stimulatory cytokines IFN-γ, TNF-α, IL-2, IL-5, IL-7, IL-1β, IL-6, IL-8, IL-12p70, IL-17A and GM-CSF at Weeks 1 and 2 post-infusion (n = 6). Of 9 patients who have been tested, 29/92 plasma proteins showed significant differences between dose levels 1 and 2, including increased IL-7 ( p <0.0004) and CD40L ( p <0.046) and reduced IL-4 ( p <0.0004). T cell receptor sequencing showed expansion and persistence of clones detected in infusion products. In summary, TAAT have thus far been safe and elicit immune responses in vivo. Clinical and immunologic response assessments are ongoing.